2015
DOI: 10.3748/wjg.v21.i22.6944
|View full text |Cite
|
Sign up to set email alerts
|

Study of celiac artery variations and related surgical techniques in gastric cancer

Abstract: AIM:To investigate celiac artery variations in gastric cancer patients and the impact on gastric cancer surgery, and also to discuss the value of the ultrasonic knife in reducing the risk caused by celiac artery variations. METHODS:A retrospective analysis was conducted to investigate the difference in average operation time, intraoperative blood loss, number of harvested lymph nodes, average postoperative drainage within 3 d, and postoperative hospital stay between the group with vascular variations and no va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 27 publications
(25 reference statements)
0
14
0
2
Order By: Relevance
“…Celiac artery variations are said to increase both the difficulty and the risk of radical gastrectomy. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Celiac artery variations are said to increase both the difficulty and the risk of radical gastrectomy. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Arterial variants are also important in gastric cancer surgery since radical gastrectomy with extensive lymphadenectomy (requiring resection of lymph nodes around the LGA, CTr and hepatic arteries) becomes standard practice. Huang et al (2015) compared groups with and without CTr variations and found that in operations on the variant group, the duration was significantly prolonged and intraoperative bleeding and postoperative drainage were significantly increased. Moreover, the LGA has to be ligated and cut off, leading to liver dysfunction if there is an aberrant LHA deriving from it.…”
Section: Discussionmentioning
confidence: 99%
“…A funnel plot with this study removed is given in Data S6. Data regarding complete celiac trunks with visceral collaterals were described in eight studies (Araujo Neto et al, 2015;Awad et al, 2017;Farghadani et al, 2016;Huang et al, 2015;Khan et al, 2017;Kornafel et al, 2010;Marco-Clement et al, 2016;Ramanand et al, 2018). From a total of 2,493 complete celiac trunks there were T A B L E 1 Overview of the variations Only one study investigated the parietal collaterals of the celiac trunk.…”
Section: Sensitivity Analysismentioning
confidence: 99%